2014
DOI: 10.1002/adsc.201400040
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine‐Free, Efficient Double Carbonylation of Aryl Iodides with Amines Catalyzed by Water‐Insoluble and Water‐Soluble N‐Heterocyclic Carbene–Amine Palladium Complexes

Abstract: The water-insoluble and water-soluble Nheterocyclic carbene (NHC)-amine palladium complexes, Ipr-PdA C H T U N G T R E N N U N G (deba)Cl and SO 3 -Ipr-PdA C H T U N G T R E N N U N G (deba)Cl, were synthesized. Both catalysts exhibit excellent activity in the phosphine-free double carbonylation of aryl iodides with amines to produce a-keto amides. Moreover, as the water-soluble catalyst exhibits significant compatibility in the aqueous phase with the activities of different Pd-NHC complexes, we con-clude that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…38 1,2-Bis(2,6-diisopro-pylphenylimino)ethane was synthesized from 1,3-bis(2,6-diisopropylphenyl)amine according to literature procedures. 39 Fe(CO)5 (Sigma Aldrich, trace metal basis), Fe2(CO)9, Fe3(CO)12 and Ph3SiCl (all abcr GmbH) were bought and used as received. 1 H NMR spectra were recorded on Bruker spectrometers operating at 200, 300, 400 or 500 MHz; 13 13 C NMR chemical shifts are reported relative to SiMe4 using the 1 H (residual) and 13 C chemical shifts of the solvent as a secondary standard (C6D6: δ 7.16 for 1 H, δ 128.06 for 13 C; CD2Cl2: δ 5.32 for 1 H, δ 53.50 for 13 C).…”
Section: Methodsmentioning
confidence: 99%
“…38 1,2-Bis(2,6-diisopro-pylphenylimino)ethane was synthesized from 1,3-bis(2,6-diisopropylphenyl)amine according to literature procedures. 39 Fe(CO)5 (Sigma Aldrich, trace metal basis), Fe2(CO)9, Fe3(CO)12 and Ph3SiCl (all abcr GmbH) were bought and used as received. 1 H NMR spectra were recorded on Bruker spectrometers operating at 200, 300, 400 or 500 MHz; 13 13 C NMR chemical shifts are reported relative to SiMe4 using the 1 H (residual) and 13 C chemical shifts of the solvent as a secondary standard (C6D6: δ 7.16 for 1 H, δ 128.06 for 13 C; CD2Cl2: δ 5.32 for 1 H, δ 53.50 for 13 C).…”
Section: Methodsmentioning
confidence: 99%
“…(entry 13, Table ). When palladacycle 6 , an IPr analogue of palladacycle 3 a , was utilized, only 58 % yield was observed, which further confirmed that ylidenes derived from acenaphthoimidazolium salts showed better catalytic activity than their imidazolium analogues owing to their stronger σ‐donor and weaker π‐acceptor properties.…”
Section: Figurementioning
confidence: 99%
“…Transition‐metal‐catalyzed carbonylation of aryl halides or pseudohalides, established in 1974 by Heck and co‐workers, has served as a most potent methodology for the synthesis of carboxylic acids and their derivatives. On the other hand, activation of inert C–H bonds is a very attractive but difficult goal in synthetic chemistry; however, with the correct selection of catalyst and substrate it can be achieved Even so, carbonylation of C–H bonds presents a great challenge and is an attractive field.…”
Section: Introductionmentioning
confidence: 99%